Mediating roles of leukoaraiosis and infarcts in the effects of unilateral carotid artery stenosis on cognition - Kuo-Lun Huang; Kuo-Lun Huang; Ting-Yu Chang; Ting-Yu Chang; Yi-Ming Wu; Yi-Ming Wu; Yeu-Jhy Chang; Yeu-Jhy Chang; Hsiu-Chuan Wu; Hsiu-Chuan Wu; Chi-Hung Liu; Chi-Hung Liu; et al. (Frontiers in Aging Neuroscience, 2022)
Background and objectivesLeukoaraiosis and infarcts are common in patients with carotid artery stenosis (CAS), and CAS severity, leukoaraiosis and infarcts all have been implicated in cognitive impairments. CAS severity was not only hypothesized to directly impede specific cognitive domains, but also transmit its effects indirectly to cognitive function through ipsilateral infarcts as well as periventricular leukoaraiosis (PVL) and deep white matter leukoaraiosis (DWML). We aimed to delineate the contributions of leukoaraiosis, infarcts and CAS to different specific cognitive domains.Materials and methodsOne hundred and sixty one participants with unilateral CAS (>50%) on the left (n = 85) or right (n = 76) side and 65 volunteers without significant CAS (<50%) were recruited. The PVL, DWML, and infarct severity were visually rated on MRI. A comprehensive cognitive battery was administered and standardized based on age norms. Correlation and mediation analyses were adopted to examine the direct and indirect influence of CAS, leukoaraiosis, and infarct on specific cognitive domains with adjustment for education, hypertension, diabetes mellitus, and hyperlipidemia.ResultsCarotid artery stenosis severity was associated with ipsilateral leukoaraiosis and infarct. Left CAS had direct effects on most cognitive domains, except for visual memory and constructional ability, and transmitted its indirect effects on all cognitive domains through ipsilateral PVL, and on constructional ability and psychomotor through infarcts. Right CAS only had negative direct effects on visual memory, psychomotor, design fluency and color processing speed, and transmitted its indirect effects on visual memory, word and color processing speed through ipsilateral infarcts. The trends of direct and indirect cognitive effects remained similar after covariate adjustment.ConclusionLeft and right CAS would predominantly lead to verbal and non-verbal cognitive impairment respectively, and such effects could be mediated through CAS-related leukoaraiosis and infarct. Given that cognition is subject to heterogeneous pathologies, the exact relationships between markers of large and small vessel diseases and their composite prognostic effects on cognition requires further investigation.